Globalization in Reducing Energy Intensity: Evidence from ASEAN Countries - Suksai, Chanatip; Panyasiri , Chaiyanant (Journal of Applied Economics and Management Strategy, 2024)
This paper investigates the effects of globalization on energy intensity in the ASEAN region from 2010-2020. Employing the panel data regression analysis to analyze the secondary dataset from the World Bank and Worldwide Governance Indicators, the results found that globalization, precisely through trade openness and FDI, significantly affects energy intensity in the ASEAN region. This suggests that heightened trade openness is linked to lower energy intensity; when a country becomes more engaged in international trade, its energy intensity decreases. Globalization considerably encourages adopting energy-efficient practices, enabling businesses to minimize operational costs. Meanwhile, FDI helps enhance operational efficiency, optimize energy usage in production processes, and reduce energy intensity. This paper contends that policies emphasizing the importance of globalization, particularly in promoting trade openness and FDI, are essential for facilitating a regional energy transition. ASEAN member states are advised to boost trade openness, liberalization, and policies related to FDI by reducing barriers and simplifying customs procedures. Enforcing stringent environmental standards for industries, especially those attracting FDI, will guarantee adherence to sustainable energy practices, resulting in increased energy efficiency and lower energy intensity across various business domains in the region.